2020
DOI: 10.1038/s41598-020-64957-7
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality clinical-experimental tests of compassion treatment techniques to reduce paranoia

Abstract: Paranoia may build on negative beliefs held both about the self and others. Compassionate imagery may be one way of reducing such negative beliefs, and hence paranoia. Two studies tested this idea, one targeting compassion for the self and one targeting compassion for others. Two-hundred individuals from the general population scoring highly for paranoia were recruited. The studies used a randomised controlled experimental design, with embedded tests for mediation. Study one targeted self-compassion via creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Fewer studies have explored virtual reality treatments beyond exposure therapy, with the exception of skills training, which has also demonstrated positive results 99 . Pilot studies have also shown that virtual reality applications can guide people to learn therapeutic skills such as mindfulness 100‐102 , relaxation 103 and self‐compassion 104,105 . Using virtual reality as a vehicle to deliver experiences that help people develop skills to manage mental health difficulties may increase treatment engagement and efficacy.…”
Section: Tools and Technologiesmentioning
confidence: 99%
“…Fewer studies have explored virtual reality treatments beyond exposure therapy, with the exception of skills training, which has also demonstrated positive results 99 . Pilot studies have also shown that virtual reality applications can guide people to learn therapeutic skills such as mindfulness 100‐102 , relaxation 103 and self‐compassion 104,105 . Using virtual reality as a vehicle to deliver experiences that help people develop skills to manage mental health difficulties may increase treatment engagement and efficacy.…”
Section: Tools and Technologiesmentioning
confidence: 99%
“…Negative self-beliefs are also strongly associated with a lack of self-compassion [ 13 ]. Experimental manipulations have found that self-compassion interventions can reduce both negative beliefs [ 14 , 15 ], and paranoia in non-clinical [ 16 , 17 ] and clinical samples [ 18 ]. Compassionate interventions focused on beliefs about others also show promise.…”
Section: Introductionmentioning
confidence: 99%
“…In students with unselected levels of paranoia, compassionate imagery techniques led to improvements in self-compassion, self-esteem and paranoia (Lincoln et al, 2013). In people from the general population reporting high levels of paranoia, compassionate imagery led to large effect size improvements in self-compassion and paranoia (Brown et al, 2020). A mediation analysis indicated that change in self-compassion explained 57% of the change in paranoia.…”
Section: Introductionmentioning
confidence: 93%